Software Requirement Specification Sistem Informasi MBKM berdasarkan Hasil Survey terhadap Sivitas Akademik - Susilowati, Meme; Kurniawan, Yudhi; Prasetiya, Hendro Poerbo; Setiawan, Rudy (SMARTICS Journal, 2024)
The MBKM (Merdeka Belajar Kampus Merdeka) policy is motivated to prepare students to know social, cultural, world of work and technological advances that have been so rapid. Competence of students must be prepared to answer the needs of the times. Link and match activities are one of the strategies used, not only with the business world and the industrial world, but also with a future that is changing so rapidly. Information Systems Study Program has implemented several programs contained in the guidelines for the implementation of the Independent Learning Campus, although on a limited scale, namely the cross-study student exchange program and the Internship program. It is necessary to make adjustments to the programs that have been implemented in Study Program to adjust the curriculum of the study program and to survey the academic community. This survey needs to be carried out to find out how far the responses, responses and knowledge of the academic community towards MBKM activities. From the results of the survey, the Study Program followed up by designing an information system for the development and strengthening of the results of the academic community for MBKM activities in the form of a Software Requirement Specification. With this Information System Design, it is hoped that it will provide convenience for the development of the Integrated MBKM information system so that it can provide convenience for the academic community in carrying out MBKM activities within the Study Program environment and also to support MBKM governance and management.